Legume consumption is inversely associated with type 2 diabetes incidence in adults: A prospective assessment from the PREDIMED study. Issue 3 (June 2018) - ,; Serra-Mir, M.; Pérez-Heras, A.; Viñas, C.; Casas, R.; Medina-Renom, A.; Baena, J.M.; García, M.; Oller, M.; Amat, J.; Duaso, I.; García, Y.; et al.
Summary: Background & aims: Legumes, a low-energy, nutrient-dense and low glycemic index food, have shown beneficial effects on glycemic control and adiposity. As such, legumes are widely recommended in diabetic diets, even though there is little evidence that their consumption protects against type 2 diabetes. Therefore the aim of the present study was to examine the associations between consumption of total legumes and specific subtypes, and type 2 diabetes risk. We also investigated the effect of theoretically substituting legumes for other protein- or carbohydrate-rich foods. Methods: Prospective assessment of 3349 participants in the PREvención con DIeta MEDiterránea (PREDIMED) study without type 2 diabetes at baseline. Dietary information was assessed at baseline and yearly during follow-up. We used Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for type-2 diabetes incidence according to quartiles of cumulative average consumption of total legumes, lentils, chickpeas, dry beans and fresh peas. Results: During a median follow-up of 4.3 years, 266 new cases of type 2 diabetes occurred. Individuals in the highest quartile of total legume and lentil consumption had a lower risk of diabetes than those in the lowest quartile (HR: 0.65; 95% CI: 0.43, 0.96; P- trend = 0.04; and HR: 0.67; 95% CI: 0.46–0.98; P- trend = 0.05, respectively). A borderline significant association was also observed for chickpeas consumption (HR 0.68; 95% CI: 0.46, 1.00; P -trend = 0.06). Substitutions of half a serving/day of legumes for similar servings of eggs, bread, rice or baked potato was associated with lower risk of diabetes incidence. Conclusions: A frequent consumption of legumes, particularly lentils, in the context of a Mediterranean diet, may provide benefits on type 2 diabetes prevention in older adults at high cardiovascular risk. Trial registration: The trial is registered athttp://www.controlled-trials.com (ISRCTN35739639). Registration date: 5th October 2005.